Intermittent Versus Continuous Low-Energy Diet in Patients With Type 2 Diabetes: Protocol for a Pilot Randomized Controlled Trial - McDiarmid, Sarah; Harvie, Michelle; Johnson, Rhona; Vyas, Avni; Aglan, Azza; Moran, Jacqui; Ruane, Helen; Hulme, Amanda; Sellers, Katharine; Issa, Basil (JMIR Research Protocols, 2021)
BackgroundIntensive face-to-face weight loss programs using continuous low-energy diets (CLEDs) providing approximately 800 kcal per day (3347 kJ per day) can produce significant weight loss and remission from type 2 diabetes (T2D). Intermittent low-energy diets (ILEDs) and remotely delivered programs could be viable alternatives that may support patient choice and adherence. ObjectiveThis paper describes the protocol of a pilot randomized controlled trial to test the feasibility and potential efficacy of remotely supported isocaloric ILED and CLED programs among patients with overweight and obesity and T2D. MethodsA total of 79 participants were recruited from primary care, two National Health Service hospital trusts, and a voluntary T2D research register in the United Kingdom. The participants were randomized to a remotely delivered ILED (n=39) or CLED (n=40). The active weight loss phase of CLED involved 8 weeks of Optifast 820 kcal/3430 kJ formula diet, followed by 4 weeks of food reintroduction. The active weight loss phase of ILED (n=39) comprised 2 days of Optifast 820 kcal/3430 kJ diet and 5 days of a portion-controlled Mediterranean diet for 28 weeks. Both groups were asked to complete 56 Optifast 820 kcal/3430 kJ days during their active weight loss phase with an equivalent energy deficit. The diets were isocaloric for the remainder of the 12 months. CLED participants were asked to follow a portion-controlled Mediterranean diet 7 days per week. ILED followed 1-2 days per week of a food-based 820 kcal/3430 kJ diet and a portion-controlled Mediterranean diet for 5-6 days per week. Participants received high-frequency (weekly, fortnightly, or monthly depending on the stage of the trial) multidisciplinary remote support from a dietitian, nurse, exercise specialist, and psychologist via telephone or the Oviva smartphone app. The primary outcomes of the study were uptake, weight loss, and changes in glycated hemoglobin at 12 months. An outcome assessment of trial retention was retrospectively added. Secondary outcomes included an assessment of adherence and adverse events. A qualitative evaluation was undertaken via interviews with participants and health care professionals who delivered the intervention. ResultsA total of 79 overweight or obese participants aged 18-75 years and diagnosed with T2D in the last 8 years were recruited to the Manchester Intermittent and Daily Diet Diabetes App Study (MIDDAS). Recruitment began in February 2018, and data collection was completed in February 2020. Data analysis began in June 2020, and the first results are expected to be submitted for publication in 2021. ConclusionsThe outcomes of the MIDDAS study will inform the feasibility of remotely delivered ILED and CLED programs in clinical practice and the requirement for a larger-scale randomized controlled trial. Trial RegistrationInternational Standard Randomized Controlled Trial Number (ISRCTN) 15394285; http://www.isrctn.com/ISRCTN15394285 International Registered Report Identifier (IRRID)DERR1-10.2196/21116